Dynamic Recrystallization (DRX) Analysis of Heavy Reduction Process with Extra‐Thickness Slabs. Issue 5 (27th December 2013) - Zhao, Xinkai; Zhang, Jiongming; Lei, Shaowu; Wang, Yuanning
<x xml:space="preserve">Abstract</x> Limited by reduction radio, heavy plates manufactured from slabs are always subjected to deterioration of soundness and mechanical properties. For overcoming these defects, in the current works, a new approach, named Heavy Reduction Process to Improve Segregation and Porosity (HRPISP), was presented. The aim this study was to investigate the process of rear heavy reduction, felling only one segment, at the end of slab solidification (about 0.85 solid fraction in the centerline). According to the real production condition of superheat, casting speed and spray intensity, a two‐step strategy was preceded using software THERCAST3D firstly. Then, a special forging simulation product FORGE3D had been used, based on the end results of THERCAST3D, to simulate the rear heavy reduction process. Results showed the distribution of temperature, strain and strain rate under both types of segment. Interestingly, something valuable had been found. After the analysis of dynamic recrystallization (DRX) model, derived from the slabs hot uniaxial compressive tests, it revealed that a certain degree of XDRX was existed. In addition, there were significant differences in distribution of XDRX volume fraction and grain size. The results of such studies provided some valuable information on the parameters of heavy reduction and the design of reduction segment.